Nanoscale Chemical Imaging of Nanoparticles under Real‐World Wastewater Treatment Conditions. (5th May 2021) - Gomez‐Gonzalez, Miguel A.; Koronfel, Mohamed A.; Pullin, Huw; Parker, Julia E.; Quinn, Paul D.; Inverno, Maria D.; Scott, Thomas B.; Xie, Fang; Voulvoulis, Nikolaos; Yallop, Marian L.; Ryan, Mary P.; Porter, Alexandra E.
Abstract: Understanding nanomaterial transformations within wastewater treatment plants is an important step to better predict their potential impact on the environment. Here, spatially resolved, in situ nano‐X‐ray fluorescence microscopy is applied to directly observe nanometer‐scale dissolution, morphological, and chemical evolution of individual and aggregated ZnO nanorods in complex "real‐world" conditions: influent water and primary sludge collected from a municipal wastewater system. A complete transformation of isolated ZnO nanorods into ZnS occurs after only 1 hour in influent water, but larger aggregates of the ZnO nanorods transform only partially, with small contributions of ZnS and Zn‐phosphate (Zn3 (PO4 )2 ) species, after 3 hours. Transformation of aggregates of the ZnO nanorods toward mixed ZnS, Zn adsorbed to Fe‐oxyhydroxides, and a large contribution of Zn3 (PO4 )2 phases are observed during their incubation in primary sludge for 3 hours. Discrete, isolated ZnO regions are imaged with unprecedented spatial resolution, revealing their incipient transformation toward Zn3 (PO4 )2 . Passivation by transformation(s) into mixtures of less soluble phases may influence the subsequent bioreactivity of these nanomaterials. This work emphasizes the importance of imaging the nanoscale chemistry of mixtures of nanoparticles in highly complex, heterogeneous semi‐solid matrices for improved prediction of their impacts on treatment processes, and potential environmental toxicity following release. Abstract : Intermediate Zn species within municipal wastewater environments are imaged using: i) discrete 9‐energy X‐ray fluorescence speciation maps and ii) X‐ray absorption near edge structure analysis. A complete transformation of isolated ZnO nanorods into ZnS occurs after only 1 hour in influent water, while preferential transformation toward Zn3 (PO4 )2 phases is observed during their incubation in primary sludge.